2007
DOI: 10.5380/rsa.v8i4.9881
|View full text |Cite
|
Sign up to set email alerts
|

GERMINAÇÃO DE Melocactus bahiensis (CACTACEAE) EM DIFERENTES SUBSTRATOS E TEMPERATURAS

Abstract: RESUMOAs sementes de diferentes espécies apresentam comportamento variável para a temperatura e o substrato no processo de germinação, o que pode fornecer informações de interesse biológico e ecológico. Com relação às espécies tropicais, muito pouco se conhece sobre as exigências das sementes quanto aos diversos fatores envolvidos na germinação, sendo assim o objetivo do trabalho foi avaliar a influência da temperatura e substrato na germinação de sementes de Melocactus bahiensis. As germinações foram analisad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 2 publications
3
9
0
14
Order By: Relevance
“…In another study with C. jamacaru, the maximum germination for this species was observed at 30 °C in white light, corresponding to 95.8 % of germination (Meiado et al, 2010). Additionally, for globose cactus Melocactus bahiensis, the highest germination percentage and germination speed index were detected at 25 °C (Lone et al, 2007). The highest germination for C.jamacaru seeds at 25 °C was corroborated with other sudy with the same species performed by Guedes et al (2009).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In another study with C. jamacaru, the maximum germination for this species was observed at 30 °C in white light, corresponding to 95.8 % of germination (Meiado et al, 2010). Additionally, for globose cactus Melocactus bahiensis, the highest germination percentage and germination speed index were detected at 25 °C (Lone et al, 2007). The highest germination for C.jamacaru seeds at 25 °C was corroborated with other sudy with the same species performed by Guedes et al (2009).…”
Section: Resultssupporting
confidence: 65%
“…This result indicate the light influence on growth parameters, reinforcing the light dependency during C.jamacaru initial seedling development. Similarly, Lone et al (2007) observed the lowest height value at 20 °C on paper substrate for Melocactus bahiensis. In a study that also involved C. jamacaru, the seedling height was higher at 25 and 30 ºC for seeds germinated in a roll of paper, whereas the seedling dry mass value was higher at 30 and 20-30 ºC, regardless of the substrate (Guedes et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Relação contrária foi observada por Lone et al (2007) em Melocactus bahiensis, no qual os valores de tempo mé-dio de germinação tiveram decréscimo conforme o aumento da temperatura de 20 para 30 o C.…”
Section: Resultsunclassified
“…Em diversos trabalhos foi verificado que a temperatura ótima para germinação de semente de cactos é, normalmente, em torno de 25 ºC (Nobel, 1988;Rojas-Aréchiga & Vázquez-Yanes, 2000;Lone et al, 2007) (Dau & Labouriau, 1974), um cacto com folhas e porte primitivo.…”
Section: Introductionunclassified
“…Os dados foram submetidos à análise de variância e as médias, comparadas pelo teste de Scott-Knott a 5% de probabilidade. (LONE et al, 2007).…”
Section: Introductionunclassified